IMPLEMENTING CORI STRATEGY IN TEACHING EXPOSITORY READING TEXT TO 12TH GRADE STUDENTS - Devi Sofiani; Annisa Astrid; Husnaini Husnaini (Universitas Lambung Mangkurat, 2026)
Reading comprehension is a crucial skill that supports academic achievement, yet it remains a significant challenge for many Indonesian students, particularly when engaging with complex expository texts. Prior studies have shown the effectiveness of the Concept-Oriented Reading Instruction (CORI) strategy in enhancing reading comprehension at various educational levels. However, research focusing on its application among twelfth-grade students is still limited. This study aims to investigate the effectiveness of implementing the CORI strategy to improve reading comprehension among twelfth-grade students in Sumatera. This research employed a quantitative method with a true experimental design. The population was all of the twelfth-grade students. The sample was selected using convenience sampling. Two groups were involved: the experimental group taught using the CORI strategy and the control group taught using the skimming technique. The data were collected using pre-test and post-test reading comprehension assessments consisting of expository texts. The results were analyzed using paired-sample and independent-sample t-tests through SPSS 27. The findings revealed a statistically significant improvement in the reading comprehension scores of students taught using the CORI strategy. Moreover, there was a significant difference in post-test scores between the experimental and control groups, indicating the effectiveness of CORI compared to the skimming technique. The study concludes that the CORI strategy is effective in enhancing students’ expository reading comprehension and recommends its implementation for senior high school instruction.